Effect of taurine on rat Achilles tendon healing. (August 2015) - Akdemir, Ovunc; Lineaweaver, William C.; Cavusoglu, Turker; Binboga, Erdal; Uyanikgil, Yigit; Zhang, Feng; Pekedis, Mahmut; Yagci, Tugay
Abstract Taurine has anti-inflammatory and antioxidant characteristics. We have introduced taurine into a tendon-healing model to evaluate its effects on tendon healing and adhesion formation. Two groups of 16 rats underwent diversion and repair of the Achilles tendon. One group received a taurine injection (200 mg/ml) at the repair site, while the other group received 1 ml of saline. Specimens were harvested at 6 weeks and underwent biomechanical and histological evaluation. No tendon ruptured. Average maximum load was significantly greater in the taurine-applied group compared with the control group (p < 0.05). Similarly, average energy uptake was significantly higher in the taurine-applied group compared with the control group (p < 0.05). We observed no significant differences in stiffness in both groups (p > 0.05). After histological assessment, we found that fibroblast proliferation, edema, and inflammation statistically decreased in the treatment group (p < 0.05). These findings could indicate greater tendon strength with less adhesion formation, and taurine may have an effect on adhesion formation.